An Update on the Role of Nitric Oxide in the Neurodegenerative Processes of Parkinson's Disease - Javier Jiménez-Jiménez, Félix; Alonso-Navarro, Hortensia; Trinidad Herrero, María; García-Martín, Elena; A.G. Agúndez, José (Current Medicinal Chemistry, 2016)
Background: The pathogenesis of Parkinson’s disease (PD) is not fully understood. Together with some important physiological functions in the Central Nervous System (CNS), nitric oxide (NO) can have both, neuroprotective or neurotoxic actions, depending on its redox state. An important body of evidence suggests the involvement of NO in many of the processes leading to neurodegeneration in several neurological disorders including PD. Objective: The main aim of this review is to update the data regarding the possible involvement of NO in the pathogenesis of PD. Methods: We performed a literature review on neuropathological, biochemical and genetic studies in PD patients and in several experimental models of parkinsonism and role of NO in these models. Results: Both studies in humans and in experimental models of parkinsonism give support to the contribution of NO in excitotoxicity, inflammation, oxidative stress, mitochondrial function impairment, DNA damage, and Snitrosylation of diverse proteins. The interaction of these mechanisms leads finally to neuronal death. The fact that selective of specific inhibitors of NO synthase (NOS, the enzyme responsible of NO synthesis) should prevent neuronal death through their actions of these pathogenic mechanisms supports the role of NO on PD as well. Conclusion: NO participates in the pathogenesis of PD by multiple mechanisms described in this review.
Keywords: Parkinson’s disease